Customary Negeri Government Without Government Critical Analysis On The Case Of Customary Negeri Government In Central Maluku District) - Wahab Tuanaya; Marno Wance (Universitas Sultan Ageng Tirtayasa, 2024)
This research aims to analyze and describe the definitive government vacuum in customary lands and the role of the Central Maluku district government in the succession of government leadership in the lands. The problems in this research are: (1) What are the issues causing the definitive government vacuum in customary villages and negeris? And (2), what is the role of the Central Maluku District government in the succession of government leadership in customary villages? The results of this research are theoretically expected to enrich the literature regarding the customary government vacuum due to problems with the mata rumah parenta (clan heredity), which are the descendants of the customary land ancestors, and the role of local governments in the succession of government leadership in customary villages and negeris. Practically, the results of this research are expected to be an input for the district government in assigning the acting village heads to fill the void in the customary land government. For this reason, the selected informants are those who are considered to have closeness to and clear knowledge of the data and information needed at the research location. The data collected from the field used in-depth interview techniques and was analyzed qualitatively. It was found that there was still a government vacuum in the existing customary villages caused more by customary problems (the matarumah parenta problem), which could not be resolved by the acting village heads on behalf of the local government. This fact describes the less optimal work of the acting village heads in carrying out their role during their years of service and their extended periods afterward.